Report 1983-84 - Planning Commission (Planning Commission, 1983)
The Annual Plan document for 1983-84 was prepared and published. On the basis of the discussions held with the Central Ministries between November 1983 and January. 1984, the outlays for the Annual Plan 1984-85 of the Centre were finalised, and sanction letters issued to the various Ministries communicating their respective Annual Plan outlays. The Mid-term appraised of the Sixth Plant covering the progress of the Plan over the first three years was prepared during the year and presented to Parliament on the 19th August 1983. The work relating to formulation of the Seventh Five Year Plan (1985— 90) has been initiated. As a first step, a series of internal discussion papers were prepared and discussed in the Planning Commission. These discussions centred around issues which would be important for preparing an Approach to the Seventh Plan. Discussions have also been held with the Panel of Economists to advise the Commission (appointed in March 1983), with representative organisations of industry and with members of Parliament who are members of the Consultative Committee attached to the Ministry of Planning. CONTENTS Pages I . Introduction (iii) II. Parliamentary Committee Meetings (v) III. (a) Annual Plan 1984-85 1 (b) Mid-Term Appraisal of the Sixth Plan 1980-85 . 1 (c) Seventh Plan—Approach Paper—Workings Groups . 1 IV. Programme Evaluation Organisation 2 V. Activities of the Divisions : (1) Perspective Planning Division 5 (2) Economic Division 6 (3) International Economic Unit 6 (4) Financial Resources Division 7 (5) Project Appraisal Division 8 (6) Monitoring and Information Division 9 (7) Agriculture Division 10 (8) Rural Development and Cooperation Division 11 (9) Irrigation & Command Area Development Division 12 (10) Multi-Level Planning Division 12 (11) Power and Energy Division 13 (12) Industry and Minerals Division 14 (13) Village and Small Industries Division 15 (14) Housing, Urban Development and Water Supply Division 16 (15) Transport Division 16 (16) Education Division 17 (17) Science and Technology Division 19 (18) Health and Family Welfare Division 19 (19) Social Welfare and Nutrition Division 20 (20) Backward Classes Division 20 (21) Labour, Employment and Manpower Division 21 (22) State Plans Division 22 (23) Statistics and Surveys Division 23 (24) Indo Japan Study Committee 23 (25) 20-Point Programme Cell 23 (26) Communications, Information and Broadcasting Division 24 (27) Plan Information and Publicity Division 25 (28) Socio-Economic Research Unit 26 (29) Use of Hindi 28 (30) Library 29 (31) Administration 29 VI. Grants-in-aid 31 ANNEX I. Number of Deputations/Delegations sent abroad 35 ANNEX II. Working/Steering/Study Groups set up for the Formulation of the Seventh Plan 39 ANNEX III. Organisational Chart 46
Government of India Planning Commission New Delhi